Applications of immobilized lipases in enzymatic reactors: A review - Remonatto, Daniela [UNESP]; Miotti, Rodney H. [UNESP]; Monti, Rubens [UNESP]; Bassan, Juliana C. [UNESP]; de Paula, Ariela Veloso [UNESP] (Elsevier, 2022)
Lipases are efficient biocatalysts with numerous applications in different industrial sectors, such as pharmaceutical, food, and fine chemistry industries. Enzyme immobilization further extends the applications of lipases by enhancing stability, selectivity, and half-life. However, obtaining high catalytic efficiency in reactions catalyzed by immobilized lipases requires optimization of reaction conditions (presence or absence of organic solvents, temperature, medium viscosity) and operational characteristics. This is a technical review focused on exploring the state-of-the-art of industrial applications of immobilized lipases in different reactor systems. Articles published between 2015 and 2020 were selected and analyzed to identify the major factors affecting the application of immobilized lipases, such as types of enzyme support, enzyme–support interactions (immobilization methods), substrate characteristics, and reactor configurations. The most common reactor configurations are discussed, as well as their advantages and disadvantages. In the current literature, studies on immobilized lipases and enzymatic reactors focus on developing strategies to minimize mass transfer limitations and eliminate the need for organic solvents.
Keywords: Bioreactor; Fluidized bed reactor; Immobilization; Lipase; Packed bed reactor; Stirred tank reactor